The Effect of ESG Performance on Profitability among Companies Listed on the Indonesian Stock Exchange - Irma Agusti; Idil Rakhmat Susanto; Safri Haliding (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
The growing emphasis on sustainable business practices has increased the importance of Environmental, Social, and Governance (ESG) performance as a strategic factor influencing corporate financial outcomes. However, empirical findings regarding the relationship between ESG performance and profitability remain inconclusive, particularly in emerging markets. This research investigates the effect of ESG performance on profitability among companies included in the IDX ESG Leaders Index during the 2022–2024 period. A quantitative approach was employed using secondary data obtained from annual reports and sustainability reports. The sample consisted of 17 non-financial companies selected through purposive sampling, resulting in 51 firm-year observations. ESG performance was measured based on disclosure indicators aligned with the Global Reporting Initiative (GRI) framework, while profitability was proxied by Return on Assets (ROA). Data were analyzed using descriptive statistics, classical assumption tests, and simple linear regression with SPSS version 25. The findings reveal that ESG performance has a positive and statistically significant effect on profitability, with a regression coefficient of 24.376 and a significance value of 0.006. The coefficient of determination (R²) of 0.144 indicates that ESG performance explains 14.4% of the variation in profitability, while the remaining variation is influenced by other factors outside the model. These results reinforce stakeholder and signaling theories, suggesting that effective ESG implementation contributes to stronger financial performance and long-term corporate sustainability.